UPAYA MENINGKATKAN AKTIVITAS BELAJAR DAN KEMAMPUAN PEMAHAMAN MEMBACA TEKS BAHASA INGGRIS MELALUI MODEL DISCOVERY LEARNING PADA PESERTA DIDIK KELAS VIII 1 SMP NEGERI 3 KOTO BARU - Erita Erita (Dharmas Education Journal (DE_Journal), 2022)
Considering that science is currently developing very rapidly, efforts are needed to improve students' reading comprehension skills, especially in English. The purpose of this study was to improve learning activities and reading comprehension skills of English texts in students whose level of learning activity and reading comprehension levels were still low at SMPN 3 Koto Baru through the discovery learning model using the stages and cycles of class action research formulated by Kurt Lewin's model. These stages include planning, action, observation, reflection or evaluation. This research was carried out in two cycles with three meetings in each cycle. As a data collection tool is the result of observing student learning activities as well as daily assessments of learning texts in cycle I and cycle II. Research shows a positive effect, namely increasing student learning activities. The average value of the percentage of student learning activities in the initial conditions is 29% and 48.75% in the first cycle to 76.67% in the second cycle, and the total value of student learning outcomes in the initial conditions is 46.5 and 51.73 in the first cycle to 74.3 in the second cycle. Thus, this study can be used as an alternative learning to improve students’ learning activities and have an impact on reading comprehension.